Analisis Kesiapan Masyarakat Dalam Pelaksanaan Program Sertifikasi Tanah Secara Elektronik: Suatu Tinjauan Sosiologi Hukum - Japar, Muhammad; Riyanto, Slamet; Fahruddin, Muhammad; Hermanto (Rechtsregel : Jurnal Ilmu Hukum, 2024)
Technological advances in Era 4.0 have encouraged the Indonesian Government to implement technology-based public services, including in the land sector with the enactment of ATR/BPN Ministerial Regulation Number 1 of 2021 concerning Electronic Certificates. Land certificates previously in physical form are now being converted into digital documents to increase efficiency, reduce land disputes, and increase legal certainty. This research aims to analyze public participation and perceptions of electronic certificates and the obstacles faced in their implementation. The method used is normative legal research with an analytical approach to legal concepts and statutory regulations as well as in-depth interviews with 10 informants from various backgrounds. The research results show that some people have started using electronic certificates, but there are still those who are hesitant because they are worried about digital data security and lack technology skills. Several respondents acknowledged the benefits of electronic certificates in facilitating the land ownership process but emphasized the importance of better data protection. The main obstacles in implementing electronic certificates are uneven internet infrastructure and networks, as well as the public's lack of technology knowledge. This research provides an important contribution to understanding the legal aspects and community readiness in facing the digitization of land certificates in Indonesia.